Greenhouse gas emissions from sheep excreta deposited onto tropical pastures in Kenya - Zhu, Yuhao; Butterbach-Baul, Klaus; Merbold, Lutz; Odour, Collins Ouma; Gakige, Jesse Kagai; Mwangi, Paul; Leitner, Sonja (ILRI, 2023)
Sub-Saharan Africa (SSA) is home to approximately 25% of the global livestock population and as estimated, contributes to 25% of the greenhouse gas emissions (GHG) from manure left on pasture section globally. However, the estimation is based on emission estimates derived from temperate regions with most of the studies being based cattle. The role of sheep manure on GHG emission needs to be verified, especially in SSA.